Sleep duration and age-related macular degeneration: a cross-sectional and Mendelian randomization study - Lei, Shizhen; Liu, Zhouyang; Li, Haihui (Frontiers in Aging Neuroscience, 2023)
Purpose: To investigate the association between sleep duration and age-related macular degeneration (AMD). Design: Cross-sectional study, bidirectional two-sample Mendelian randomization (MR). For cross-sectional analysis, we used survey data of 5, 481 participants aged ≥ 40 years from the 2005-2008 National Health and Nutrition Examination Survey (NHANES). For MR analysis, we used sleep-and AMD-associated genome-wide association studies (GWAS) data involving large populations. Methods: The association between sleep duration and AMD was assessed using logistic regression models. For MR analysis, the primary approach for MR analysis was the inverse-variance weighted (IVW) method. Results: In cross-sectional analysis, after adjusting for multiple covariates, short sleep duration (SSD) was found to be associated with increased risk of early AMD (odds ratio [OR] = 1.364, P = 0.036). MR analysis supported the results of cross-sectional analysis: SSD increases the risk of early AMD (beta = 0.102, IVW-P = 0.003). Conclusion: Our findings provide the evidence supporting the association between sleep deficiency and higher risk of AMD. Further studies are required to confirm our findings and elucidate the mechanisms underlying this association.